The impact of COVID-19 on education in Ghana - Upoalkpajor, Joshua-Luther Ndoye; Upoalkpajor, Cornelius Bawa (Brazilian Journal of Implantology and Health Sciences, 2020)
This study was intended to examine the effect of COVID-19 on education in Ghana. This study was guided by the following objectives; to evaluate the awareness of COVID-19 virus among students in Ghana, to examine the impact of COVID-19 on education in Ghana and to evaluate the after effect of COVID-19 epidemic on education system in Ghana. The study employed the descriptive and explanatory design; questionnaires in addition to library research were applied in order to collect data. Primary and secondary data sources were used and data was analyzed using the chi square statistical tool at 5% level of significance which was presented in frequency tables and percentages. The respondents under the study were 100 teachers and students of selected Senior High Schools (SHS) in Tamale metropolitan area of northern region of Ghana. The study findings revealed that COVID-19 pandemic has significant impact on education in Ghana; based on the findings from the study, schools want resources to reconstruct the loss in education through the epidemic.